The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.langmuir.3c00595
|View full text |Cite
|
Sign up to set email alerts
|

Superior Selective CO2 Adsorption and Separation over N2 and CH4 of Porous Carbon Nitride Nanosheets: Insights from GCMC and DFT Simulations

Abstract: Development of high-performance materials for the capture and separation of CO2 from the gas mixture is significant to alleviate carbon emission and mitigate the greenhouse effect. In this work, a novel structure of C9N7 slit was developed to explore its CO2 adsorption capacity and selectivity using Grand Canonical Monte Carlo (GCMC) and Density Functional Theory (DFT) calculations. Among varying slit widths, C9N7 with the slit width of 0.7 nm exhibited remarkable CO2 uptake with superior CO2/N2 and CO2/CH4 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(78 reference statements)
1
1
0
Order By: Relevance
“…The results indicate that the adsorption of CO 2 on MCER and D001 is simple physical adsorption, and this is consistent with the experimental data that the adsorption capacity of CO 2 on MCER (1.87 mmol/g) is greater than that of CO 2 on D001 (1.07 mmol/g). , The adsorption energies of the CO 2 molecules in MCER-DEA and D001-PEI are −17.59 and −18.64 kcal/mol, respectively. These values are close to B 38 fullerene (−15.96 kcal/mol) and Ni-decorated InN (−15.22 kcal/mol) but greater than the results of C 9 N 7 (−6.46 kcal/mol) and Se-doped graphene (−5.01 kcal/mol) . Considering that the E ads of CO 2 on a high-performance adsorbent are preferably between −9.78 kcal/mol and −19.57 kcal/mol, the MCER-DEA and D001-PEI are thus effective CO 2 storage adsorbents.…”
Section: Resultssupporting
confidence: 93%
“…The results indicate that the adsorption of CO 2 on MCER and D001 is simple physical adsorption, and this is consistent with the experimental data that the adsorption capacity of CO 2 on MCER (1.87 mmol/g) is greater than that of CO 2 on D001 (1.07 mmol/g). , The adsorption energies of the CO 2 molecules in MCER-DEA and D001-PEI are −17.59 and −18.64 kcal/mol, respectively. These values are close to B 38 fullerene (−15.96 kcal/mol) and Ni-decorated InN (−15.22 kcal/mol) but greater than the results of C 9 N 7 (−6.46 kcal/mol) and Se-doped graphene (−5.01 kcal/mol) . Considering that the E ads of CO 2 on a high-performance adsorbent are preferably between −9.78 kcal/mol and −19.57 kcal/mol, the MCER-DEA and D001-PEI are thus effective CO 2 storage adsorbents.…”
Section: Resultssupporting
confidence: 93%
“…There are many different components in actual combustion products such as H 2 O, SO 2 and NO X . Aside from the toxicity itself, these gases also have strong interactions with sorbents, decreasing the CO 2 capture capacity of the sorbent over subsequent cycles [4][5][6][7][8][9][10][11]. Rege et al [12] found that the presence of water could reduce the adsorption capacity in the adsorption process because of its strong adsorption force.…”
Section: Introductionmentioning
confidence: 99%